2011
DOI: 10.1051/0004-6361/201014899
|View full text |Cite
|
Sign up to set email alerts
|

Infrared emission from the composite grains: effects of inclusions and porosities on the 10 and 18 μm features

Abstract: Aims. In this paper we study the effects of inclusions and porosities on the emission properties of silicate grains and compare the model curves with the observed infrared emission from circumstellar dust. Methods. We calculated the absorption efficiency of the composite grain, made up of a host silicate oblate spheroid and inclusions of ice/graphite/or voids, in the spectral region 5.0-25.0 μm. The absorption efficiencies of the composite spheroidal oblate grains for three axial ratios were computed using the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…The DDA is expected to be accurate, as long as the interdipole separation, d , is small compared with the wavelength of the incident radiation [see also Purcell and Pennypacker , ; Vaidya and Gupta , ]. As indicated in Table , in our calculations, d is set to be 0.01 µm, which fits this criterion.…”
Section: Resultsmentioning
confidence: 99%
“…The DDA is expected to be accurate, as long as the interdipole separation, d , is small compared with the wavelength of the incident radiation [see also Purcell and Pennypacker , ; Vaidya and Gupta , ]. As indicated in Table , in our calculations, d is set to be 0.01 µm, which fits this criterion.…”
Section: Resultsmentioning
confidence: 99%
“…It is seen that the absorption efficiencies increase with volume fraction of SiC and there is no appreciable shift in the wavelength of peak absorption at 10µm feature. In our earlier study Vaidya & Gupta (2011), using DDA, we have shown the variation of absorption efficiencies of composite grains with inclusions of graphite and porous silicate grains.…”
Section: Model Absorption Curves and Absorption Efficiency Of Composimentioning
confidence: 91%
“…AR = 1.33 and volume fraction of f=0.1. Please see Table 1 in Vaidya & Gupta (2011) and also Chýlek et al (2000). The DDA code generates a three dimensional matrix, specifying the material type at each dipole site.…”
Section: Composite Grain Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…We use the modified computer code (Vaidya et al 2001, Vaidya & Gupta 2011 to generate the composite grain models. We have studied composite grain models consisting of a host silicate spheroid and inclusions of graphite or other carbonaceous materials (e.g.…”
Section: Composite Grain Modelmentioning
confidence: 99%